The Effect of Gamma Rays on the Main Static Characteristics of SiGe Transistors (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2017)
The article considers the effect of 60Co gamma rays on the characteristics (the major ones for the analog ICs) of SiGe n-p-n transistors of SGB25V technology: the voltage across the forward-biased base-emitter junction, the dependence of the static base current gain in the common-emitter (CE) configuration on emitter current, the output characteristic in the CE configuration.